Simulation-based analysis method for damage survivability of passenger ships. Issue 3 (2nd September 2019) - Ruponen, Pekka; Lindroth, Daniel; Routi, Anna-Lea; Aartovaara, Marja
ABSTRACT: A new approach for analysing the level of survivability for a passenger ship in the event of a collision damage is presented. Monte Carlo simulation is used for generating a large number of damage cases. The probability distributions for damage extent and location are based on the current SOLAS regulation. Each case is calculated with time-domain flooding simulation, assuming quasi-static motions and calm sea, thus enabling evaluation of the righting lever curve during the flooding process. The ship survivability is analysed based on requirements for a sufficient reserve stability. The proposed method is demonstrated with a large passenger ship design. Based on the detailed investigation of the results, the effects of various design changes are studied. Furthermore, the impact of waves on the flooding process is studied. The presented method for survivability assessment is robust and especially suitable for comparing design variations, or ships with similar main dimensions.